Photocatalytic interaction of aminophylline–riboflavin leads to ROS‐mediated DNA damage and cell death: A novel phototherapeutic mechanism for cancer. Issue 8 (21st June 2017) - Khan, Saniyya; Naseem, Imrana
Abstract: The accompanied tissue devastation and systemic toxicity of chemotherapy has shifted the quest for having an effective and palliative cancer therapy towards photodynamic therapy (PDT). Riboflavin (Rf), an essential micronutrient is emerging as a potent tool of PDT, due to its excellent photosensitizing properties. It can be used as an efficient adjuvant for various anticancer drugs. The hemolytic and proteolytic effect of photoilluminated aminophylline (Am), a xanthine derivative, and Rf is well documented in literature. In this study, using human peripheral lymphocytes we have demonstrated the strong pro‐oxidant effects of photocatalytic interaction between Am and Rf. The photo degradation kinetics of Am in the presence of Rf was monitored using UV spectroscopy, fluorescence spectroscopy, and Fourier transform infrared spectroscopy. The resultant pro‐oxidant action of Am was monitored through various assays like lipid peroxidation, protein carbonylation, and reactive oxygen species (ROS) generation. Furthermore, the cytotoxic potential of this system was studied using comet and MTT (3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide) assay. Treated lymphocytes were visualized using fluorescence and scanning electron microscopy to further validate apoptosis. ROS scavengers ameliorated the oxidative damage caused by this system suggesting pivotal role of ROS in causing apoptotic cell death. As cancer cells exhibit increased absorption of Rf as well as are very sensitive in any further ROS level increment, this putative pathway can serve as an effective anodyne phototherapeutic strategy for cancer treatment. © 2017 IUBMB Life, 69(8):611–622, 2017